West Teleservice - Petersen, Mitchell A.; O'Keef, Robert (London : Kellogg School of Management, 2014)
Between the mid-1980s and 1996, the amount that U.S. companies spent on teleservices grew from around $34 billion to nearly $80 billion. Of those expenditures, the portion outsourced to specialized teleservices firms had grown from almost nothing to about $6 billion. The outsourced portion was widely expected to grow at a 50 percent annual rate through 2001. Several large teleservices firms planned to capitalize on this growth. From mid-1995 through November 1996, seven pure-play teleservices firms tapped the public equity market with initial public offerings, some returning to the market with secondary and tertiary offerings. By the end of November 1996 the combined market capitalization of these seven firms equalled $6.7 billion. The firms collectively traded at 6.2 times 1996 sales and 108 times 1996 earnings. The case focuses on West Teleservice's IPO and students are asked to consider what the price should be for 5.7 million shares that are about to publicly traded.
Originally published in Peterson, M. A., & O'Keef, R. (2014). West Teleservice. 5-104-020. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; West Teleservice; Telephone answering services